The Influence of Job Satisfaction, Job Conflict and Work Stress on Employee Performance in The Council of Representative Office - Ratnawita Ratnawita; Zulkifli; Luh Kadek Budi Martini; Fitri Nur Mahmudah; Syahribulan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study intends to examine the relationship between workplace conflict, stress, and employee performance. The Slovin technique was employed to determine the sample size for this study, and a margin of error of 10% was used, resulting in the usage of 60 individuals as the research sample. Multiple linear regression is the data analysis method used, and the SPSS program is used. According to the study's findings, employee performance is impacted by work conflict, stress, and job satisfaction all at once. Work conflict, stress, and job satisfaction are all shown to have an impact on employee performance.